Temporal analyze of the soil use and comparison between the NDVI and SAVI indexes in the city of Santa Cruz do Rio Pardo - SP using Landsat-5 images - DEMARCHI, Julio Cesar; PIROLI, Edson Luís; ZIMBACK, Célia Regina Lopes (UFPR, 2011)
The current essay intends to analyze the temporal soil use evolution in the city of Santa Cruz do Rio Pardo – SP through the supervised classification of the satellite images Landsat-5 TM according to the maximum likelihood, as well as verify the mapping accuracy by Kappa coefficient, compare the NDVI and SAVI vegetation indexes in different understanding factors for the canopy substrate and determine the vegetal cover percentage in all methods used on 05-26-2007, 01-07-2009 and 04-29-2009. The Maxver classification showed clearly several spatial changes in the soil use in the considered period. The most appropriated vegetation indexes were the NDVI and SAVI – 0,25 factor, which showed similar values of vegetal cover percentage, but discrepant in respect to the inferred value for MAXVER classification.